Clinical and Demographic Pro?le of Diarrheal Patients of Pediatric Age: A Cross-Sectional Study - Ekta Acharya (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background : Sometimes, diarrhea may co-exist with vomiting, fever, abdominal pain, etc. depending upon its etiology. Diarrheal diseases can also lead to significant malnutrition and dehydration. Thus, at the tertiary care center, a study was conducted with an aim to center on the clinical and sociodemographic profile of infants and children presenting with acute diarrhea. Subjects and Methods: It was a prospective, observational clinical study that began after obtaining approval from the Institutional Ethics Committee. It was conducted at the Department   of Pediatrics, Gujarat Adani Institute of Medical Science, Bhuj, Kutch for a period of 2 years. The sample size was 200 with 2 groups A and    B having 100 patients each. Accordingly, their clinical and demographic profile was also noted and studied in 2 groups. Various parameters analyzed were age and gender distribution, chief complaints, feeding practices, nutritional status and assessment of dehydration. Results: Mean age S.D were (2.25 1.40) and (2.49 1.39) years in group A and B respectively. Exclusive breastfeeding (EBF) for 6 months was given in a  large no. of group A and B patients i.e. 52 (52%) and 58(58%) respectively. Few others were given for 4, 5, or 7 months. Maximum patients 58 (58%) of A and 52 (50%) of B group had no dehydration whereas remaining 42 (42%) and 48 (48%) patients had some dehydration respectively. Conclusion: Fever and vomiting were the complaints mainly regularly linked with diarrhea. a bit fewer than half of the children under research had some-dehydration. Greater parts of the patients were completely breastfed for six months.